Cohesin: its roles and mechanisms. - Nasmyth, K; Haering, C (2009)
The cohesin complex is a major constituent of interphase and mitotic chromosomes. Apart from its role in mediating sister chromatid cohesion, it is also important for DNA double-strand-break repair and transcriptional control. The functions of cohesin are regulated by phosphorylation, acetylation, ATP hydrolysis, and site-specific proteolysis. Recent evidence suggests that cohesin acts as a novel topological device that traps chromosomal DNA within a large tripartite ring formed by its core subunits.